The analysis of the transition from university to work after graduation in social science subjects with special focus on Pakistan - Ghulam Rasool, Dahri, Dr. (Universiti Malaysia Perlis, 2009)
Organized by Centre for Communication Skills and Entrepreneurship UniMAP in collaboration with The Ministry of Higher Education Malaysia, 5th - 6th December 2008 at Putra Palace Hotel, Perlis.